O princípio da sanabilidade na comparticipação processual e a jurisprudência defensiva - Cavati, Taís Dias (2016)
This dissertation intends to study the principle of “remediable nullities” that exist at the process model of comparticipation, verifying if this promotes the search of the primacy of merit, in a way that make possible evaluate your influence in the judgement of admissibility of the Courts. Therefore, will be considered the different methodological stages experienced by the civil procedural law , as well as different process models adopted, in order to highlight the current situation as regards the Constitutional Civil Procedure. Furthermore, the main principles of Coparticipation will be examined, including a vision of how this was applied in the new Civil Procedure Code. At the central part of the dissertation will be detached the evaluative formalism and will be evidenced the importance of privileging merit, surpassing the excess of unnecessary formalities. Analyzing the instrumentality of the legal forms and the judgement of admissibility of the appeals, will bring to a conclusion if the coparticipation process will avoid the defensive case law.